A Study on the Relationship between Concept Mapping and Reflective Thinking - Yadav, Pushpendra (JOURNAL OF INDIAN EDUCATION, 2020)
Concept mapping is a graphical organising technique, and it also work as a reflective tool for students as well as teachers and teacher educators. In the present scenario, learning outcomes is a big concern for any classroom. In this research paper, researcher wants to investigate the relationship of concept mapping and reflective thinking, and also want to analyse on the basis of gender and how much relationship has shifted in which direction? For fulfillment of this purpose, researcher selected three schools (one government and two private) from Ajmer city and selection was done through the sample purposive sampling. Researcher selected 48 boys’ students and 28 girls’ students and the total sample was 76 students. Researcher used descriptive statistics and inferential statistics for analysing the data. In inferential statistics, researcher used Pearson’s bivariate correlation. Findings of this research paper highlighted that there is a minimal difference in relationship of concept mapping and reflective thinking on the basis of gender, and this difference indicates towards other factors.